Comparison of relative and absolute values of magnetic resonance imaging in the diagnosis of spinal epidural lipomatosis. (4th July 2019) - Ge, Yuxi; Yang, Xiaohan; You, Yaqian; Xuan, Yinghua; Yan, Gen
Abstract : Objective: To describe spinal epidural lipomatosis (SEL) of the lumbar region and evaluate the relative versus absolute values of epidural fat (EF) to determine which is more appropriate when using magnetic resonance imaging (MRI). Design: Comparative study. Setting: Hospital. Participants: Eight SEL patients and 40 healthy adults. Interventions: MRI measurement of EF. Outcome Measures: The MRI-based EF thickness, cutoff value, and coefficient of variation (CV) were calculated. Frequency distribution maps for the absolute EF value and the relative EF/DuS value were created. Results: SEL involved L3 − L4 in all cases. The mean EF thickness was 12.11 ± 2.28 mm (range: 9.91 − 16.86 mm), and the average diameter of the dural sac (DuS) was 20.02 ± 2.64 mm; the EF/DuS ratio was 0.61 ± 0.03. In controls, the average EF thickness was 7.35 ± 1.68 mm (range: 4.81 − 10.92 mm), and the average DuS was 20.86 ± 2.11 mm; the EF/DuS ratio was 0.35 ± 0.08. The relative and absolute values were significantly higher in the SEL group than in the normal group. A cutoff value of 9.8 mm could distinguish SEL patients from normal individuals. For the SEL group, the CV of the relative values (4.9%) was lower than that of the absolute values (18.8%). The frequency distribution map showed that the distribution of relative values was more concentrated than that of the absolute values for both groups. Conclusion: Based on the frequency distribution and CVs, the relative value of EF/DuS maybe a better measure for diagnosing SEL than the absolute EF value.